SUB-NATIONAL INNOVATION POLICY: A UNIVERSAL ENTITLEMENT TO EDUCATION GRANT IN SABANG, INDONESIA - Renaldi Safriansyah (Fakultas Ilmu Sosial dan Ilmu Pemerintahan, 2021)
This article studies a universal entitlement to education grant policy in Sabang that shows the exercise of discretionary power by a local government in Indonesia. The policy has been initiated by Sabang municipality of Aceh province to help students at primary and secondary schools who would otherwise struggle with the cost of education. Desk study and semi- structured interviews were conducted with the major and high-ranking officials from related government departments in Sabang. The results show the transfer of authority and responsibility under the decentralization is instrumental in supporting policy initiation and policy formulation at local level. Sub-national governments at a special region and a frontier region were given an authority to design an educational policy that ensure all students have better access to education. While mandatory financial functions of local authorities have not always been well defined, responsibility for establishing an education grant has not been easy to be understood, especially by lower tier of governments. However, Sabang Education Grant (SEG) has been evidence of how a municipality government exercise its discretionary power in decision-making. To implement such innovation policy, Sabang municipality government established the institution, regulate the operational procedures, provide the technical guideline, and developed the tools for internal controls.